Prophylactic Positive End-Expiratory Pressure and Postintubation Hemodynamics: An Interventional, Randomized Study - Olivier Lesur; Marie-Anaïs Remillard; Catherine St-Pierre; Simon Falardeau (Canadian Respiratory Journal)
OBJECTIVE: To investigate the hemodynamic and outcome effects of implementing prophylactic positive end-expiratory pressure (PEEP) versus zero end-expiratory pressure (ZEEP) in patients during the postintubation period in the emergency setting.